Prophets without honour at home: A view from the margins (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
This article is a personal reflection on how serving as a lecturer of an African language at a multi-lingual South African university has been like thus far for the author. In its narrative and perhaps even autobiographical mode, the article further encapsulates the author’s formative influences towards pursuing, studying, teaching and writing in an African language (Tshivenḓa) within an academic sphere of South Africa. Furthermore, the article foregrounds the challenges faced by a novice lecturer and scholar in marginalised languages such as Tshivenḓa, which include, among others, the lack of intensive mentorship in the teaching and learning of Tshivenḓa, limited opportunities to publish in scholarly and accredited journals, students’ and lecturers’ negative perceptions towards the mother-tongue, minimal reviewers and examiners of journal articles, research proposals, dissertations and theses written in Tshivenḓa. Apart from airing the author’s grievances, the article also vanguards the author’s hope that African languages such as Tshivenḓa will eventually move from the margins to the centre of epistemic and other forms of pedagogic discourse within the South African context, and perhaps even beyond. To this end, some opinions on how this hope can be fulfilled are provided.